A Recent Advance in Teak Culture - Mahmood Hussain, A. M.; Somasundaram, T. R.; Subramanian, K. N. (Indian Forester, 1976)
A new finding of research at the Regional Forest Research Centre, Coimbatore is reported. Sprouting teak buds nipped off from stock stumps and planted in polythene containers in the glass house have developed into independent plants with healthy root systems. With refinement of technique, stock plants may cease to be indispensable for the propagation of scion material.